Unsur Fisik dan Batin pada Puisi “Kita” “Aku Menunggu Bunga” “Kita Berjalan Berdua” dan “Mengetuk Ketukan” Karya Heri Isnaini - Tintin Rohaeni; Elsa Mayori (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This study aims to reveal the physical and spiritual elements in Heri Isnaini's poems, namely "Kita", "Aku Menunggu Bunga", "Kita Jalan Berdua", and "Mengetuk Ketukan". In terms of physical elements, the analysis includes diction, imagery, concrete words, figures of speech, rhyme, and typography used by the poet to build the beauty and meaning of the poem. Spiritual elements include themes, feelings, tones, and messages that reflect the poet's attitude towards life, love, and human existence. The results of the analysis show that Heri Isnaini uses a lot of simple but meaningful diction, as well as metaphors and personifications that strengthen the emotional nuances. Visual imagery and feelings are dominant in creating a deep poetic atmosphere. Themes such as waiting, togetherness, love, and the search for the meaning of life are the common thread of the entire poem. With a stylistic and hermeneutic approach, it can be concluded that these poems not only reveal the poet's personal expression, but also reflect universal human experiences.